Selective determination of metal chlorocomplexes in saline waters by magnetic ionic liquid–based dispersive liquid–liquid microextraction: Selective determination of metal chlorocomplexes in saline waters by magnetic ionic liquid–based dispersive liquid–liquid microextraction - Herce-Sesa, Belén; López-López, José A.; Moreno, Carlos (Analytical and bioanalytical chemistry, 2025)
In this work, we explore a new dispersive liquid–liquid microextraction (DLLME) method to selectively separate chemical species of Cd and Zn in saline waters. It is based on the use of the magnetic ionic liquid (MIL) methyltrioctylammonium tetrachloroferrate ([N 1,8,8,8 + ][FeCl 4 − ]), which allows an efficient and environmentally friendly extraction of the target species. In addition, the paramagnetic component in the MIL simplifies the separation step required in DLLME, allowing for fast separation and recovery of the extracted species with a magnet, without a centrifugation step. The optimum conditions for the separation by MIL-DLLME were 3.3 mg mL −1 MIL, sample pH = 8, and an extraction time of 30 min. Under these conditions, metal chlorocomplexes (99.7% and 81.0% of total metal concentration for Cd and Zn, respectively) were quantitatively separated, remaining the free cations in the aqueous samples. In a second step, the extracted metal species were back-extracted with 1 mol L −1 HNO 3 and a re-extraction time of 15 min. For cadmium, this acidic solution separated the neutral complex CdCl 2 (60.5%), while CdCl + (21.5%) and CdCl 3 − (18.1%) remained in the organic phase. For Zn, the anionic complex ZnCl 3 − (17.3%) was retained by the organic reagent, while ZnCl 2 (45.7%) and ZnCl + (37.0%) were re-extracted by the nitric acid solution. The separation of the chemical species of metals along the three liquid phases used allowed their quantification in several samples of real seawater and a certified reference material. Graphical Abstract